2013
DOI: 10.1091/mbc.e13-06-0315
|View full text |Cite
|
Sign up to set email alerts
|

The Hsp70/90 cochaperone, Sti1, suppresses proteotoxicity by regulating spatial quality control of amyloid-like proteins

Abstract: Escape of aberrant proteins from protein quality control leads to accumulation of toxic protein species. Sti1 interacts with Hsp70 to mediate spatial PQC of amyloid-like proteins by regulating their distribution in different intracellular protein-handling depots. Sti1 suppresses proteotoxicity by targeting amyloid-like proteins to perinuclear foci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 72 publications
2
67
1
1
Order By: Relevance
“…Toxic Htt103Q aggregates consisted of many small puncta, whereas protective Htt103Q aggregates consisted of large foci at the IPOD. In another report, the sequestration of Htt103Q into Sti1 foci, a juxtanuclear site distinct from the JUNQ and IPOD, also reduced toxicity (36). Thus, irrespective of their subcellular localization, the formation of large Htt103Q foci seems to be protective against toxicity.…”
Section: Discussionmentioning
confidence: 90%
“…Toxic Htt103Q aggregates consisted of many small puncta, whereas protective Htt103Q aggregates consisted of large foci at the IPOD. In another report, the sequestration of Htt103Q into Sti1 foci, a juxtanuclear site distinct from the JUNQ and IPOD, also reduced toxicity (36). Thus, irrespective of their subcellular localization, the formation of large Htt103Q foci seems to be protective against toxicity.…”
Section: Discussionmentioning
confidence: 90%
“…Besides being associated with aggregates, Hsp110 was enriched in a manner correlating with the relative toxicity of the aggregates when overexpressed in a human cell lineage (Olzscha et al 2011). Other proteins also seem to collaborate with Hsp110 in a system that recovers protein aggregates in the cell, including HOP, and small Hsps (Rampelt et al 2012, Mattoo et al 2013, Torrente and Shorter 2014, Wolfe et al 2013. By overexpressing amyloid-like aggregates in a human cell model, Olzscha et al (2011) showed that Hsc70 and its co-chaperones Hsp110, Hsp40/ Hdj1/2, and Bag2 associated with the aggregates.…”
Section: Shifting Paradigms On Aggregate Resolubilization In Metazoansmentioning
confidence: 99%
“…Cytoprotection may involve several mutually non-exclusive effects. First, controlled deposition of soluble misfolded proteins can reduce their cytotoxicity (Arrasate et al 2004;Cheng et al 2007;Cohen et al 2006;Cohen et al 2009;Walther et al 2015;Wolfe et al 2013). Second, it might prevent exhaustion of the protein quality control machinery during protein folding stress, by confining the sticky surfaces of misfolded proteins.…”
Section: Sequestration Of Misfolded Proteins As Protective Strategymentioning
confidence: 99%